A randomized controlled study for the treatment of acne vulgaris using high-intensity 414 nm solid state diode arrays. (4th July 2015) - Ash, Caerwyn; Harrison, Anna; Drew, Samantha; Whittall, Rebecca
Abstract: The treatment of acne vulgaris poses a challenge to the dermatologist, and the disease causes emotional anxiety for the patient. The treatment of acne vulgaris may be well-suited to home-use applications, where sufferers may be too embarrassed to seek medical treatment. This randomized controlled study is designed to quantify the effectiveness of using a blue light device in a therapy combined with proprietary creams, in the investigation of a self-treatment regimen. A total of 41 adults with mild-to-moderate facial inflammatory acne were recruited. The subjects were randomly assigned to combination blue light therapy ( n = 26) or control ( n = 15). Photography was used for qualitative assessment of lesion counts, at weeks 1, 2, 4, 8, and 12. All subjects in the treatment cohort achieved a reduction in their inflammatory lesion counts after 12 weeks. The mean inflammatory lesion counts reduced by 50.02% in the treatment cohort, and increased by 2.45% in the control cohort. The reduction in inflammatory lesions was typically observable at week-3, and maximal between weeks 8 and 12. The treatment is free of pain and side-effects. The blue light device offers a valuable alternative to antibiotics and potentially irritating topical treatments. Blue light phototherapy, using a narrow-band LED light source, appears to be a safe and effective additional therapy for mild to moderate acne.